High Prevalence of Hepatitis B Virus Infection Among People With HIV in Rural and Periurban Communities in Botswana. (6th January 2023) - Phinius, Bonolo B; Anderson, Motswedi; Gobe, Irene; Mokomane, Margaret; Choga, Wonderful T; Mutenga, Sharon R; Mpebe, Gorata; Pretorius-Holme, Molly; Musonda, Rosemary; Gaolathe, Tendani; Mmalane, Mompati; Shapiro, Roger; et al.
Abstract: Background: We aimed to determine the prevalence of hepatitis B virus (HBV) infection among people with human immunodeficiency virus (PWH) in rural and periurban communities in Botswana. Methods: PWH from a previous population-based study, the Botswana Prevention Combination Project, which enrolled adults in 30 communities across Botswana (2013–2018), were screened for HBV surface antigen (HBsAg) and HBV core antibody (anti-HBc). HBsAg-positive (HBsAg + ) samples were further screened for HBV core immunoglobulin M antibodies (anti-HBc immunoglobulin M [IgM]) and HBV e antigen (HBeAg). We quantified HBV viral load on participants who tested positive (n = 148) and negative for HBsAg (n = 381). Results: Of 3304 participants tested, 271 (8% [95% confidence interval CI, 7%–9%]) were HBsAg + while 1788 (56% [95% CI, 54%–57%]) of 3218 PWH whom we tested had positive anti-HBc. Approximately 88% of HBsAg + participants were on antiretroviral therapy (ART), 40% and 56% of whom were receiving lamivudine- and tenofovir-containing ART, respectively. Male sex (relative risk ratio [RRR], 1.8 [95% CI, 1.2–2.7]) and the northern geographic region (RRR, 2.5 [95% CI, 1.4–4.7]) were independent predictors of HBV infection (HBsAg + ). Of 381 persons with negative HBsAg who were tested for occult HBV, 126 (33% [95% CI, 29%–38%]) had positive HBV DNA. Eleven participants were highly viremic with high HBV viral load while on a lamivudine- or tenofovir-containing regimen. Ten (91%) of these participants also had positive HBeAg serology, while 4 (36%) had positive anti-HBc IgM serology. Conclusions: The prevalence of HBV was high among PWH in Botswana while on ART regimens with activity against HBV. Abstract : In a near-nationwide, predominantly rural population–based random sample of >3300 adults with HIV, HBsAg and occult HBV prevalence was 8% and 33%, respectively. Male sex and the northern region were independent predictors of HBV infection in Botswana.